2006
DOI: 10.1002/14651858.cd004856.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural and cognitive behavioural therapy for obsessive compulsive disorder in children and adolescents

Abstract: Analysis 1.2. Comparison 1 BT/CBT versus waitlist or placebo, Outcome 2 Number with OCD at post treatment.. Analysis 1.3. Comparison 1 BT/CBT versus waitlist or placebo, Outcome 3 NIMH-GOCS at post treatment.. . Analysis 1.4. Comparison 1 BT/CBT versus waitlist or placebo, Outcome 4 Clinical Global Impressions-Improvement. Analysis 1.5. Comparison 1 BT/CBT versus waitlist or placebo, Outcome 5 Change in CY-BOCS prior to post.. . Analysis 2.1. Comparison 2 BT/CBT versus medication, Outcome 1 CY-BOCS score at po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
49
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(49 citation statements)
references
References 71 publications
0
49
0
Order By: Relevance
“…[74] It found significantly improved OCD symptoms (assessed by the children' . Individual or group CBT described in both RCTs involved 14 sessions (each duration 1-1.5 hours) and included the following components: psycho education, anxiety management, cognitive therapy, exposure and response prevention, resiliency building, generalisation training, and relapse prevention.…”
Section: Benefitsmentioning
confidence: 93%
See 2 more Smart Citations
“…[74] It found significantly improved OCD symptoms (assessed by the children' . Individual or group CBT described in both RCTs involved 14 sessions (each duration 1-1.5 hours) and included the following components: psycho education, anxiety management, cognitive therapy, exposure and response prevention, resiliency building, generalisation training, and relapse prevention.…”
Section: Benefitsmentioning
confidence: 93%
“…The review reported that the description of randomisation in the first RCT suggested quasi-randomisation. [74] CBT versus SRIs:…”
Section: Benefitsmentioning
confidence: 99%
See 1 more Smart Citation
“…CBT is the approach with stronger evidence of effectiveness as compared to waiting lists or attention control interventions for both OCD [163][164][165] and non-OCD pediatric anxiety disorders. [164][165][166] The overall effect size of CBT for pediatric anxiety in a meta-analysis involving 48 studies (n=3,740) was 0.66 (compared to passive control 0.77 and to active control 0.39; both significant), demonstrating a key role of non-specific factors.…”
Section: Psychotherapymentioning
confidence: 99%
“…Recent expert consensus guidelines suggest that cognitive behavioural treatments are the first choice treatments for children and adolescents with OCD [21,26] although a Cochrane review concluded only that ''behavioural or cognitive behaviour therapy (CBT) appears to be a promising treatment for OCD in children and adolescents'' [27]. Until recently, there have been few trials which examine the effectiveness of cognitive behavioural therapy for young people, based on the assumption that adult-based research would generalise.…”
Section: Introductionmentioning
confidence: 99%